Generating sentiment lexica : evaluating approaches with genetic algorithms and particle swarm optimization - Daly, Nicholas (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
This thesis examines the application of sentiment analysis towards financial news. The primary goal within the field of sentiment analysis is to develop a methodology by which the sentiment or emotional view being expressed by the author(s) of a text may be extracted and quantified.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin